Prevalencia de Parasitosis Gastrointestinales en bovinos domésticos (Bos Taurus) de la parroquia San Buenaventura en el cantón Latacunga - Rojas Llumiquinga, Alexis Marcelo (2023)
This research work was carried out in the urban parish of San Buenaventura, Latacunga, Cotopaxi province, with the objective of identifying the types of gastrointestinal parasites that occur in the parish in order to help and increase the production of small producers in the sector, the diagnostic techniques used were simple sedimentation and flotation with saline. A total of 110 samples of feces taken at random and obtained directly from the animal's rectum were analyzed, taking into account the dependent variables of age and sex of the animals. The number of sampling in males was 38 animals, with positive cases in 23 cattle with a prevalence of 60.53%. The number of sampling in females was 72 animals, with positive cases in 44 cattle with a prevalence of 61.11%. Therefore, in a total sampling number of 110 animals, there were 67 positive cases and a prevalence of 61% which indicates that it is a high percentage. The parasites with the highest prevalence are Cooperia spp and Ortegarias spp with a prevalence of 25.71%, followed by Coccidia with a percentage of 22.86%, then Haemonchus contortus with a prevalence of 9.52%, Trichostrongylus spp with a prevalence of 5.71% and finally Bunostomum spp with a prevalence of 4.76% of the total prevalence. However, Toxocara and Oesophagostomun spp. showed a lower prevalence in the sector with a percentage of 0.95%. Based on the data identified in the study, a treatment and prevention protocol was proposed to help reduce the percentage of parasitism in infected cattle, ensuring that the health conditions of the animals are the most efficient and that they can adequately fulfill their production functions.